Analisis Perbandingan Keputusan Pembelian Konsumen Sebelum Dan Sesudah Tiktok Shop Dibuka Kembali - asih endah; Mursyid; Novi Nur Akhmad (Jurnal Bisnis Administrasi dan Manajemen, 2025)
The COVID-19 pandemic has encouraged society to explore newopportunities through digitalization, particularly via social media. TikTok, as asocial media platform, integrates both social networking and marketplace featuresthrough TikTok Shop. The rise of online shopping via TikTok Shop significantlyimpacted conventional MSMEs, leading the government to officially shut it down.However, after its acquisition by GoTo, TikTok Shop was officially reopened inconjunction with the National Online Shopping Day.This study targets consumers residing in Sleman Regency who havepreviously shopped online via TikTok Shop. A comparative quantitative method wasemployed to analyze purchasing decisions before and after the reopening of TikTokShop. The study utilized purposive sampling, with purchasing decisions measuredthrough indicators such as price, promotion, and product quality. Instrumenttesting included validity tests, reliability tests, normality tests, homogeneity tests,and data analysis using the non-parametric Mann-Whitney U test.The analysis results show that the first hypothesis test yielded a significancevalue (P-value) of 0.000, indicating a significant difference. The second hypothesistest using the mean rank analysis concluded that purchasing decisions beforeTikTok Shop's reopening (122.96) were better than after its reopening (78.04).Purchasing decisions were influenced by factors such as price, promotions, andproduct quality. The majority of respondents, who work as private-sectoremployees, were sensitive to price changes and expected more promotions, such asdiscounts, free shipping vouchers, and coupons, to enhance the appeal of onlineshopping.